1999
DOI: 10.1289/ehp.99107s165
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic roles of acetylcholine.

Abstract: In the adult nervous system, neurotransmitters mediate cellular communication within neuronal circuits. In developing tissues and primitive organisms, neurotransmitters subserve growth regulatory and morphogenetic functions. Accumulated evidence suggests that acetylcholine, (ACh), released from growing axons, regulates growth, differentiation, and plasticity of developing central nervous system neurons. In addition to intrinsic cholinergic neurons, the cerebral cortex and hippocampus receive extensive innervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(71 citation statements)
references
References 68 publications
1
69
0
1
Order By: Relevance
“…During brain development, cholinergic neurons project from the nucleus basilis of Meynert to the frontal lobe [42]. Lauder and Schambra [64] reported that prenatal ethanol exposure in the mouse led to severely affected development of the forebrain CNS cholinergic system with deleterious effects on the synaptic targets of these cholinergic neurons, including reduced thickness of the cerebral cortex. The frontal lobe was significantly smaller (relative and absolute) in FAS/PFAS relative to all other groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During brain development, cholinergic neurons project from the nucleus basilis of Meynert to the frontal lobe [42]. Lauder and Schambra [64] reported that prenatal ethanol exposure in the mouse led to severely affected development of the forebrain CNS cholinergic system with deleterious effects on the synaptic targets of these cholinergic neurons, including reduced thickness of the cerebral cortex. The frontal lobe was significantly smaller (relative and absolute) in FAS/PFAS relative to all other groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Early work by Sulik and Johnston [70,71], Sulik [72], Schambra et al [23] and Lauder and Schambra [64] illustrated the teratogenic impact of alcohol on the developing cholinergic system. As reported by Lauder and Schambra [64], in the adult nervous system, neurotransmitters mediate cellular communication within neuronal circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Organophosphates (OPs) and carbamates break down the enzyme acetylcholinesterase (AChE), already lower during pregnancy (Evans et al 1988), allowing acetylycholine to build up in the neuronal junction. AChE inhibition disrupts cell replication and differentiation, synap-togenesis, and axonogenesis (Bigbee et al 2000; Lauder and Schambra 1999). It is likely that pesticides also act through noncholinergic mechanisms involving alterations in expression and function of nuclear transcription factors (Dam et al 2003).…”
mentioning
confidence: 99%
“…Эти гомеостатические механизмы вовлекают из-менения и пресинаптические и постсинаптиче-ские компоненты холинергической системы, вклю-чая высокое сродство к транспортеру холина, АХ-трансферазе и mАХ [58,148]. Многие из выше-упомянутых компенсационных механизмов участву-ют в процессе нервного развития и могут привести к нейроповеденческим отклонениям у развиваю-щихся животных [51, 63,103,106,107].…”
Section: последствия пренатального воздействия хлорорганических соедиunclassified